Preliminarily evaluation the safety and immunogenicity of tetanus, reduced diphtheria and acellular pertussis (five components) combined vaccine, adsorbed (Tdcp) in participants aged 6 years and above: a blinded and randomised, and controlled phase I clinical trial - Liu, Xiaoyu; Wei, Chen; Huang, Haitao; Wan, Jingxuan; Li, Yajun; Wang, Feiyu; Li, Siwen; Wang, Ying; Wang, Xuewen; Wang, Xue; Sui, Xiuwen; Gou, Jinbo; et al. (Frontiers in Immunology, 2025)
Pertussis remains a significant global public health challenge, particularly in China, where no licensed pertussis-containing vaccines are available for individuals aged 6 years and older. This blind, randomised, and controlled phase I clinical trial evaluated the safety and immunogenicity of the Tetanus, Reduced Diphtheria, and Acellular Pertussis (Five Components) Combined Vaccine, Adsorbed (Tdcp). Participants aged 6 years and above were divided into three age subgroups (6–11, 12–17, and ≥18 years) and randomised to receive Tdcp or control vaccines (PPV23 or DT). Safety endpoints included the incidence of adverse reactions within 30 days post-vaccination, while immunogenicity was assessed through seroconversion rates and geometric mean concentrations (GMCs) of anti-DT, TT, PT, FHA, PRN, and FIM 2&3 antibodies at 30 days post-vaccination. Among 178 participants, the incidence of total adverse reactions in the Tdcp group was 54.62%, primarily local reactions such as pain and itching, with no significant differences compared to controls (p > 0.05). Immunogenicity analysis revealed robust immune responses in the Tdcp groups, with seroconversion rates for pertussis-related antigens exceeding 75% in all age groups. The GMCs for anti-PT antibodies reached 125.60 IU/mL, 150.28 IU/mL, and 131.14 IU/mL in the ≥18 years, 12–17 years, and 6–11 years of Tdcp groups, respectively. Overall, the Tdcp vaccine demonstrated a good safety profile and robust immunogenicity in participants aged 6 years and above. The inclusion of five pertussis antigens, particularly PT, elicited strong immune responses, supporting its potential as an effective booster vaccine for adolescents and adults.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06056050.